PEAR: Protected Based Energy- Aware Routing For WSNs - Santha Devi, A; Vinoba, V (International Journal of Computer Sciences and Engineering, 2025)
Energy aware routing protocols can be ordered into energy saver and energy administrator. Energy saver protocols diminish energy utilization completely. The greater part of them attempt to locate the most limited way amongst source and goal to diminish energy utilization. Yet, energy administrator protocols adjust energy utilization in network to maintain a strategic distance from network dividing. Discovering best route just in light of energy adjusting thought may prompt long way with high postponement and declines network lifetime. Then again, discovering best route just with the briefest separation thought may prompt network apportioning. This paper enhances SEER routing protocol. Conventional SEER is just energy saver and has poor thought regarding energy adjusting. Our proposed protocol, named PEAR, considers energy adjusting and ideal separation both. It finds a reasonable tradeoff between energy adjusting and ideal separation by learning automata idea. We reproduce and assess routing protocols by NS2 simulator.